Mobile Learning Field Activity: Pedagogy of Simultaneity to Support Learning in the Open - Gallagher, Michael Sean; Ihanainen, Pekka (Proceedings of the International Conference on Networked Learning, 2014)
Mobile learning field activities are presented in this paper as a mechanism for enacting learning in the ‘open’, either in response to formal disciplinary learning activities or to support those moored in informal learning practices. Field activity represents a disciplinary model found across the (field) sciences and throughout the humanities. It has traditionally involved using disciplinary process (observation, data collection, analysis, dissemination) to research social or biological phenomena. Mobile technology has accelerated the process and potential for “coming to know” in the field by allowing the learner to engage multiple layers of meaning, social presence, time, and place simultaneously. These mobile learning field activities represent an authentic application of both informal and formal learning, and include, by way of example, learning walks, geocaching, and urban exploration. Examples presented in this paper include a mobile learning field activity presented in Helsinki, Finland. However, the context, content, and social interactions of this learning can be incredibly complex. This complexity requires a pedagogical response that acknowledges this complexity, identifies the layers of engagement and simultaneous activity taking place, and proposes strategies that maximizes the potential of learning in the open (or in the field). This paper identifies three continuums in which this simultaneous activity is taking place: the serendipity-intentionality of learner orientation, the informal-formal activity structure and the initiative-seduction-sense of intervals continuum of human presence. All three speak to the variety of learner engagements that occur as a result of mobile learning and field activity. This paper advances the belief that new pedagogical approaches are needed to account and make use of these continuums of activity. These layers overlap and are simultaneously engaged in by the learner to generate context and understanding in fluid mobile spaces. The Pedagogy of Simultaneity is proposed to account for these layers of overlap and simultaneity. It advances a pedagogical response by emphasizing human methods. These methods are enacted through trust, discussion, and collage (or composition). Teachers can generate field activities that emphasize this layered reality for learning. This pedagogy addresses the complexity and simultaneity present in mobile learning field activities and we are cautiously optimistic that it also applicable to open learning and elearning.